The Dictyostelium discoideum spore germination-specific cellulase is organized into functional domains. - Ramalingam, R (1992)
During Dictyostelium discoideum spore germination, degradation of the cellulose-containing spore wall is required to allow the amoeba to emerge. The CelA gene, which is transcribed and expressed exclusively during spore germination, codes for a 705-amino-acid protein that has cellulase activity [endo-(1,4)-beta-D-glucanase]. Amoebae transformed by a vector containing the CelA coding sequence or portions of it transcribed from a heterologous promoter expressed and secreted full-length or suitably truncated proteins during vegetative growth when, under normal conditions, these proteins are not made. The gene constructs divided the CelA protein into three domains: a 461-amino-acid N-terminal region that has significant similarity to those of other cellulases and that has been shown to be the catalytic domain; a contiguous 91-residue repeat containing the motif threonine-glutamic acid-threonine-proline, which is glycosylated; and, joined to the repeat, a C-terminal 153-amino-acid sequence that most probably defines a cellulose-binding domain.